Women's perceived risk of sexual harassment in a Bus Rapid Transit (BRT) system: The case of Barranquilla, Colombia. (September 2019) - Orozco-Fontalvo, Mauricio; Soto, José; Arévalo, Andrea; Oviedo-Trespalacios, Oscar
Abstract: Background: Sexual harassment in public transportation is a growing concern, particularly among women. Over the years, there have been several programs and policies to mitigate sexual harassment while using public transport. However, there is little evidence of the effectiveness of these strategies, especially in Latin America. Objective: This investigation aims to determine the factors that influence women's perceived risk of sexual harassment while using public transport in Colombia. Methods: In this study, we designed an image-based stated preferences survey based on the current bus rapid transit (BRT) system in Barranquilla, Colombia. Several variables were considered in this experiment including the time of the day, surveillance, and crowding, among others. For each scenario, participants reported whether they felt safe or not. Then, a logistic regression analysis was conducted to identify the factors that influence women's perceived risk of sexual harassment while using the BRT system. Results: The results show that more than 60% of respondents have been a victim of sexual harassment while using the BRT system. Also, overcrowded buses proved to have the most negative effect on the perceived risk of sexual harassment. Travelling at night, lighting and being alone were all significant variables as well. Conclusion: Sexual harassment could potentially influence use of the BRT. The findings of this research can be used to develop countermeasures and increase public transport ridership. Highlights: Sexual harassment affects public transportation ridership. Women's perceived risk of sexual harassment was modelled using logistic regression analysis. Surveillance cameras on their own do not increase perceived security for women. Overcrowded buses proved to have the most negative effect on risk perception.